Pemberdayaan Remaja melalui Edukasi Anti-Bullying Berbasis Nilai Islami sebagai Strategi Penguatan Karakter - Regina, Putri Rasta; Sirulhaq, Sirulhaq; Asep; Qoyyimah, Ai; Kodariah, Eris; Trilailani, Siti Filda; Anipah, Ani (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Bullying among junior high school students is a significant issue that disrupts psychosocial development and the learning process. This community engagement initiative focuses on empowering students at SMPN 1 Cikembar, Sukabumi Regency, through anti-bullying education grounded in Islamic values to prevent aggressive behavior and foster a harmonious school environment. The objective is to enhance the awareness of ninth-grade students regarding the adverse impacts of bullying and to instill values such as rahmah (compassion) and ukhuwah (brotherhood) as the foundation for social behavior. Employing a qualitative approach with a case study design, this initiative involved 350 students in a one-hour socialization session facilitated by students of Islamic Education (PAI). Interactive methods, including group discussions, role-plays, and in-depth interviews, were utilized for data collection, which were subsequently analyzed using the Miles and Huberman model. The results indicate a significant increase in students’ understanding of bullying, from 20% to 75%, with 65% of students actively participating in discussions. A 30% reduction in verbal conflicts was observed within one week post-session. The Islamic values-based approach proved effective in enhancing empathy, although time constraints limited long-term behavioral internalization. This engagement lays the foundation for sustainable anti-bullying programs, with recommendations for follow-up sessions and the integration of religious values into the school curriculum. The initiative contributes to fostering inclusive character development among adolescents and creating a safe school environment in rural settings.